Root Microbiota in Primary and Secondary Apical Periodontitis - Bouillaguet, Serge; Manoil, Daniel; Girard, Myriam; Louis, Justine; Gaïa, Nadia; Leo, Stefano; Schrenzel, Jacques; Lazarevic, Vladimir (Frontiers in Microbiology, 2018)
Apical periodontitis is an inflammatory disease of the dental periradicular tissues triggered by bacteria colonizing necrotic root canals. Primary apical periodontitis results from the microbial colonization of necrotic pulp tissues. Secondary apical periodontitis results from a persistent infection of incorrectly treated root canals. The aim of this study was to characterize the microbiota present in primary and secondary intra-radicular infections associated with apical periodontitis using 16S rRNA gene amplicon sequencing. Teeth exhibiting apical periodontitis with or without root canal treatment were extracted after informed consent. From each tooth, the intra-radicular content as well as a dentin sample (control) were collected and subjected to DNA extraction. PCR amplicons of the V3-V4 region of the bacterial 16S rRNA gene were pooled and sequenced (2x300) on an Illumina MiSeq instrument. The bioinformatics analysis pipeline included quality filtering, merging of forward and reverse reads, clustering of reads into operational taxonomic units (OTUs), removal of putative contaminant OTUs and assigning taxonomy. The most prevalent and abundant OTU in both dentin and root canal samples was assigned to anaerobic bacterium Fusobacterium nucleatum. Multivariate analysis showed clustering of microbiota by sample type (dentin vs intra-radicular content) and, in root canals, by pathology (primary vs secondary infection). The proportions of Enterococcus faecalis and F. nucleatum were respectively higher and lower when comparing secondary to primary infected root canals. Co-occurrence network analysis provided evidence of microbial interactions specific to the infection type. The identification of bacterial taxa differentially abundant in primary and secondary intra-radicular infections may provide the basis for targeted therapeutic approaches aimed at reducing the incidence of apical periodontitis.